QUESTIONNAIRE DESIGN USING GENERATIVE AI: A CASE STUDY FROM MARKETING - Ludvík Eger (Trendy v podnikání)
There is an ongoing exploration of Generative AI in redesigning the teaching and learning process and investigating the validity of these practices. The case study addresses this call by presenting an experience from the teaching and learning process at the Faculty of Economics. Marketing is an area where the application of AI tools is already commonly used in corporate practice. The exercise was designed to apply knowledge from marketing on the one hand, and prompt engineering on the other. The activity took place in early 2024 and proved to be a rather challenging task not easy to accomplish, especially due to the low experience of the students in prompt engineering for Generative AI. The findings of this study suggest that today's teaching and learning process at universities should be transformed to train students to be future-ready for employment in a society powered by Generative AI. The student experience of Generative AI is changing, and the use of practical activities that can be applied in future practice seems to be a valuable innovation in education.